Reading the Story of Jesus Christ as an Epic - Mwai, Wangari; Gimode, Edwin; Kebaya, Charles (Cultural and Religious Studies, 2015)
There is no doubt that Jesus Christ is the eternal embodiment of the Christian faith. The story of salvation, especially the life of Jesus, forms the basis through which many Christians encounter the eternal. Indeed, each facet of Christ is intricately intertwined with the others and that Christian literature often focuses on redefining various figures in the image of Christ and on illustrating morality. Without disparaging in any way the story of Jesus Christ, this paper parallels the conceptualization of epic heroism and the narrative of Jesus Christ. In doing this, the article provides a critical exegesis of elements of epic heroism in the story of Christ. Ultimately, reading the story of Jesus Christ through the prism of epic heroism helps us submit that it is a “tale of Christian identity” comparable to the epic identity and able to convey eternal meaning to Christian groups who recognize it as “their story of salvation”.
Keywords: Epic; Epic heroism; Jesus Christ; Christian identity